Lysosome‐Targeting Amplifiers of Reactive Oxygen Species as Anticancer Prodrugs. Issue 49 (9th November 2017) - Daum, Steffen; Reshetnikov, M. S. Viktor; Sisa, Miroslav; Dumych, Tetyana; Lootsik, Maxim D.; Bilyy, Rostyslav; Bila, Evgenia; Janko, Christina; Alexiou, Christoph; Herrmann, Martin; Sellner, Leopold; Mokhir, Andriy
Abstract: Cancer cells produce elevated levels of reactive oxygen species, which has been used to design cancer specific prodrugs. Their activation relies on at least a bimolecular process, in which a prodrug reacts with ROS. However, at low micromolar concentrations of the prodrugs and ROS, the activation is usually inefficient. Herein, we propose and validate a potentially general approach for solving this intrinsic problem of ROS‐dependent prodrugs. In particular, known prodrug 4‐( N ‐ferrocenyl‐ N ‐benzylaminocarbonyloxymethyl)phenylboronic acid pinacol ester was converted into its lysosome‐specific analogue. Since lysosomes contain a higher concentration of active ROS than the cytoplasm, activation of the prodrug was facilitated with respect to the parent compound. Moreover, it was found to exhibit high anticancer activity in a variety of cancer cell lines (IC50 =3.5–7.2 μm ) and in vivo (40 mg kg −1, NK/Ly murine model) but remained weakly toxic towards non‐malignant cells (IC50 =15–30 μm ). Abstract : Targeting cancer : A potentially general approach for improving the anticancer activity of ROS‐dependent prodrugs is presented and validated. In particular, a known prodrug was converted into its lysosome‐specific analogue. Because lysosomes contain a higher concentration of active ROS than the cytoplasm, activation of the prodrug was facilitated with respect to the parent compound.